Green Synthesis of Magnetic Nanoparticles of Iron Oxide Using Aqueous Extracts of Lemon Peel Waste and Its Application in Anti-Corrosive Coatings - Elizondo Villarreal, Nora; Verástegui Domínguez, Luz Hypatia; Rodríguez Batista, Raúl; Gándara Martínez, Eleazar; Alcorta García, Aracelia; Martínez Delgado, Dora Irma; Rodríguez Castellanos, Edén Amaral; Vázquez Rodríguez, Francisco Javier; Gómez Rodríguez, Cristian (Molecular Diversity Preservation International, 2022)
Lately, the development of green chemistry methods with high efficiency for metal nanoparticle synthesis has become a primary focus among researchers. The main goal is to find an eco-friendly technique for the production of nanoparticles. Ferro- and ferrimagnetic materials such as magnetite (Fe3O4) exhibit superparamagnetic behavior at a nanometric scale. Magnetic nanoparticles have been gaining increasing interest in nanoscience and nanotechnology. This interest is attributed to their physicochemical properties, particle size, and low toxicity. The present work aims to synthesize magnetite nanoparticles in a single step using extracts of green lemon Citrus Aurantifolia residues. The results produced nanoparticles of smaller size using a method that is friendlier to health and the environment, is more profitable, and can be applied in anticorrosive coatings. The green synthesis was carried out by a co-precipitation method under variable temperature conditions. The X-ray Diffraction (XRD) and Transmission Electron Microscopy (TEM) characterization showed that magnetite nanoparticles were successfully obtained with a very narrow particle size distribution between 3 and 10 nm. A composite was produced with the nanoparticles and graphene to be used as a surface coating on steel. In addition, the coating’s anticorrosive behavior was evaluated through electrochemical techniques. The surface coating obtained showed good anticorrosive properties and resistance to abrasion.